How to Calculate and Design Shell and Tube-type Heat Exchanger with a Single Heat Transfer - Ragadhita, Risti; Nandiyanto, Asep Bayu Dani (ASEAN Journal for Science and Engineering in Materials, 2024)
The process in the industry requires equipment with high efficiency, especially energy. This is closely related to the need to measure the heat-transfer process in heat exchangers. A study of the effectiveness of a heat exchanger is needed to increase the effectiveness of the heat exchanger because each heat exchanger product created has different effectiveness. This study aims to discuss and explain the calculations in the design of shell and tube-type heat exchangers. A step-by-step method for calculating heat exchanger designs is presented, including reviewing simple cases regarding heat exchanger design calculations. This research has the potential to be used as standard information on how to do step-by-step calculations for heat exchanger design.